1990
DOI: 10.1073/pnas.87.3.1198
|View full text |Cite
|
Sign up to set email alerts
|

Specific interaction of the human immunodeficiency virus Rev protein with a structured region in the env mRNA.

Abstract: A region of potential complex secondary structure within the human immunodeficiency virus env mRNA has been implicated in Rev-mediated export of viral structural mRNAs from the nucleus to the cytoplasm. By using an RNase protection gel-mobility-shift assay, we demonstrate that purified Rev protein forms a stable complex with this Rev-responsive RNA. RNAs with mutations designed to disrupt formation of a predicted stem structure no longer interact with Rev. However, Rev binding is restored upon annealing of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
2

Year Published

1990
1990
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(113 citation statements)
references
References 28 publications
4
107
2
Order By: Relevance
“…We and others have shown recently that purified Rev protein derived from E. coli forms a specific interaction with RRE RNA {Daly et al 1989;Zapp and Green 1989;Cochrane et al 1990a;Heaphy et al 1990;Malim et al 1990). Because of possible difficulties associated with purification of each of the 14 mutations described, the feasibility of using Rev within E. coli lysates in the binding assays was examined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We and others have shown recently that purified Rev protein derived from E. coli forms a specific interaction with RRE RNA {Daly et al 1989;Zapp and Green 1989;Cochrane et al 1990a;Heaphy et al 1990;Malim et al 1990). Because of possible difficulties associated with purification of each of the 14 mutations described, the feasibility of using Rev within E. coli lysates in the binding assays was examined.…”
Section: Resultsmentioning
confidence: 99%
“…Western blot analysis with an anti-Rev antiserum raised against a synthetic peptide corresponding to amino acids 1-20 (residues not affected by the mutagenesis) showed comparable levels of Rev protein in each lysate (data not shown). One microliter of cleared lysate was incubated with in vitro-transcribed RRE RNA transcripts, and binding was measured in a qualitative gel mobility-shift ribonuclease T1 protection assay (Cochrane et al 1990a). As shown in Figure 3, many of the Rev mutants failed to interact with the RRE RNA.…”
Section: Identification Of the Rev Rna-binding Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, bulged adenosines are present in the 16S rRNA binding sites of ribosomal proteins $8 and $15 (Garrett et al 1984). The trans-acting factor Rev of HIV-1, which is essential for the production of unspliced (-~9 kb) and singly spliced (~-4 kb)transcripts that encode viral structural proteins (for review, see Cullen andGreene 1989 andFelber 1990), was recently reported to be an RNA-binding protein (Daly et al 1989;Zapp and Green 1989;Cochrane et al 1990;Heaphy et al 1990). Its target, the Rev responsive element (RRE), forms a complex secondary structure (Dayton et al 1989), that was shown to be necessary for both Rev binding in vitro and the Rev response in vivo (Malim et al 1990;Olsen et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…However, mutating certain arginine residues in the NLS alters the nucleolar but not the nuclear localization of Rex. Several studies indicate that targeting of Rex to its correct subcellular compartment is critical for its proper function (69,70).…”
Section: Rex Proteins: Structure Subcellular Localization and Functmentioning
confidence: 99%